Robot assisted incremental sheet forming of Al6061 under static pressure: Preliminary study of thickness distribution within the deformation region - Prakash Singh R.; Kumar Gupta S.; Kumar Singh P.; Kumar S. (My University, 2025)
Incremental sheet forming (ISF) has a basic advantage over the conventional forming processes such as deep drawing in terms of increased formability of the sheet due to delayed necking as a result of localized deformation. In this process, a forming tool is mounted on the traditional CNC machines and is programmed to move so as to impart the deformation to the sheet. The non-uniform thickness distribution in the sheet and sheet thinning are among the drawbacks of the process. The use of back hydrostatic pressure provides a promising way to overcome this problem. The process called incremental sheet hydroforming (ISHF) uses back fluid hydrostatic pressure as a support to deform the sheet. In this work, the six axes industrial robot has been used for the deformation of the Al6061. The conical (with diameter 28 cm and the height 14.2 cm) and pyramidal shapes (dimension of the rhombohedral pyramid is 28 cm × 28 cm × 14 cm) with wall angle 40 degrees have been obtained by this process. The spiral tool path has been used for the shape generation and the speed of the tool was 200 mm/sec making the process faster than the conventional ISF process. The thickness variation of the sheet has been found to be more uniform as in the case of incremental sheet forming with back hydrostatic pressure. © 2021 Elsevier Ltd.